2019
DOI: 10.21577/0103-5053.20190164
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Assembled AMF-Responsive Nanoplatform Based on Pillar[5]arene and Superparamagnetic Nanoparticles for Controlled Release of Doxorubicin

Abstract: An alternating magnetic field (AMF)-stimuli responsive nanodevice based on magnetic nanoparticles (MNP) functionalized with water-soluble carboxylate-substituted pillar[5]arene (CP[5]A), namely MNP-CP[5]A, as a multiplatform for cancer treatment has been designed. MNP-CP[5]A was loaded with doxorubicin (DOX), showing a loading capacity of 9.5 mg g-1. The nanodevice demonstrated good colloidal stability, superparamagnetic behavior, and was capable to generate detectable heat in solution induced by AMF applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Owing to the water solubility and optical properties of the prepared coordinating systems, various spectroscopic methods were employed to examine the host–guest complexes in water under normal conditions. Of note, other research groups also reported coordinating materials, including synthetic organic macrocycles that coordinate drugs in organic solvents and subcritical water [ 78 , 79 ], and the assembly of an organic macrocycle and inorganic nanoparticle that coordinates drugs in water [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the water solubility and optical properties of the prepared coordinating systems, various spectroscopic methods were employed to examine the host–guest complexes in water under normal conditions. Of note, other research groups also reported coordinating materials, including synthetic organic macrocycles that coordinate drugs in organic solvents and subcritical water [ 78 , 79 ], and the assembly of an organic macrocycle and inorganic nanoparticle that coordinates drugs in water [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NOE and NOESY analyses demonstrated that the molecule was orientated with the part that contains the alcoholic groups toward the ethylene amine units and with the phenol-ether unit toward the aromatic rings of CTV. Broadening of the aromatic Doxorubicin signals in D 2 O as with the shift at highest ppm in the presence of 3a indicated the presence of more than one species undergoing a slow exchange on the 1 HNMR time scale inside and outside the CTV units [ 68 ]. The orientation of the drug molecule that interacted with 3a had also shown hydrogen bonding interactions between the alcoholic groups of Doxorubicin and amino groups of 3a .…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The functionalization of s-MS and r-MS was carried out following procedures that were well established by our group for different materials. ,,,, The activated s-MS (0.60 g) and r-MS (0.40 g) materials were added to a bottom round flask containing PhMe (60 mL) and TESBN (2.0 mL), respectively, under stirring. The dispersions were maintained under reflux and N 2 atmosphere for 2 h. Then, an aliquot of each dispersion (1.5 mL) was removed from the system with subsequent addition of TESBN (0.6 mL).…”
Section: Methodsmentioning
confidence: 99%
“…Pillararenes (P­[ n ]­A) are promiscuous molecules due to their versatile functionalization and ability to be used as hosts for several kinds and sizes of guest molecules by enlarging their cavities. For biological applications, a variety of biocompatible pillararenes have been proposed by the judicious choice of functional groups. In recent years, P­[ n ]­A have been widely explored as a component of drug delivery systems, e.g., vesicles, micelles, nanoparticles, and nanogates for switchable devices. , Previously, we demonstrated that cationic ammonium pillar[5]­arene can be used as a nanogate by interacting with spherical anionic MS nanoparticle surfaces, indicating that cationic-substituted pillar[5]­arenes are promising switchable components for blocking silica pores . To the best of our knowledge, N -methylimidazolium-pillar­[5]­arene (MIP5 + ) has not been explored as a cationic nanogate for MSNs.…”
Section: Introductionmentioning
confidence: 99%